Battle on Fake News: WhatsApp among the College Students in Chennai (Journal of Advanced Research in Journalism & Mass Communication, 2018)
WhatsApp has become a suitable victim for everything its wrong in India right now. Another move to stem the spread of fake news and misinformation through its instant messaging app, which marks “unusual” links sent on chats as “suspicious”. The Students are forward more text, photos, and videos than any other country. This study examined college students’ use of WhatsApp for spearing fake news among their circles. The study was conducted from various college Students in and around Chennai are St. Peter’s College of Engineering and Technology, DG Vaishnav College and St. Thomas College of Arts and Science. Survey method is adopted in order to analyse the usages of WhatsApp for battle on fake news among the College students in Chennai. The purpose study to know the impact of fake news changing the learning style, aggressive nature, conflict, reliability, breaking relationships, Socioeconomic status, etc. How to cite this article: Srinivasan R, Kumar TKS, IlamParithi V. Battle on Fake News: WhatsApp Among the College Students in Chennai. J Adv Res Jour Mass Comm 2018; 5(4): 66-70. DOI: https://doi.org/10.24321/2395.3810.201821